Internet connectivity disruption in Costa Rica (Costa Rica) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Costa Rica. Data sourced from IODA.
Network Disruption Incident ID: CR-2026-0006. Severity: critical. Confidence: 65%